Planejamento urbano e segregação socioespacial: estudo sobre os efeitos do processo de expansão de condomínios fechados na produção do espaço urbano - Silva, Bruno das Mercês (Universidade Federal de São Carlos, 2021)
It’s usual in brazillian’s large and medium cities the existence of a narrow relation between the production of the urban space and the planning policies. In this context, gated communities arise and get associated to the expansion of the urban space, which produce significant effects in the geographic space. This research aimed to analyze the consequences of the process of expansion of gated communities in the urban space, focusing on the effects related to the access to green areas and leisure spaces. In order to make it, starting by the theoric effort, this research proceed to a comparative study between two sub-areas that belong to the same “census” sector: a gated community whose name is Bosque Ipanema, and a suburbia whose name is Jardim Botucatu, both located in Sorocaba/ SP. Photointerpretation was used, combined to other associated methodologies, in order to produce and analyze the data. The results pointed to the existence of socio-spatial segregation related to the structure differences observed between the sub-areas, segregation that express itself especially on the access to the green areas leisure spaces.
Urban planning and socio-spatial segregation: a study on the effects of gated communities' expansion process in the production of urban space
Keywords: Urbano; Planejamento; Segregação; Áreas verdes; Lazer; Urban; Planning; Segregation; Green areas; Leisure; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA URBANA